Analyzing Trends for Girl Child Education Prospects in Urban Rajasthan - Khanduri , Shailja (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
This paper analyzes the trends in parental economical and psychological aspects visa-a-vis girl child education in urban Rajasthan. Study finds that the gender of parent is not a critical parameter for positive attitude towards girls’ education and both mother and father are equally interested in the same. Parents from urban Rajasthan are found to be having positive attitude towards girl child’s education and getting a job after completing her education, irrespective of the parent’s education level, economic well-being or awareness about gender inequality issues prevalent in society.